REPRESENTASI KOLONIALISME ISRAEL DAN RESISTANSI PALESTINA DALAM FILM 200 MITRIN KARYA AMEEN NAYFEH (2020) - Dyah Ayu Ratna Azzahra; Reza Sukma Nugraha (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
This study aims to analyze the characteristics of colonialism and forms of Palestinian resistance as depicted in the film 200 Meters, employing Albert Memmi's theory of colonialism. The film not only portrays acts of resistance but also demonstrates how colonialism shapes the identities of both the colonizer and the colonized, as seen through the protagonist Mustafa's perilous journey to reunite with his family across a 200-meter separation enforced by Israel's apartheid wall. Using qualitative descriptive analysis, this research examines Arabic-language dialogue excerpts and visual sequences from 200 Meters. Key findings include:14 instances revealing Israeli colonial characteristics, categorized as: 3 traits of colonizers in denial, 3 traits of colonizers in acceptance, 3 traits of colonized subjects in acceptance, 4 traits of colonized subjects in rejection, 7 forms of Palestinian resistance, comprising: 2 cases of primordialism, 1 rejection of colonial state symbols, 1 rejection of colonial laws, 1 assimilation attempt, 2 demonstrations of solidarity.